PERAN PERAWAT PENANGGUNG JAWAB ASUHAN (PPJA) DALAM PEMBERIAN MEDIKASI BERBASIS ENAM BENAR OBAT DI RUANG ANTHURIUM 3 RUMAH SAKIT JEMBER KLINIK - Kholid Rosyidi Muhammad Nur; Nurfika Asmaningrum; Sri Wahyuni; Sindi Arika Putri (Health and Technology Journal (HTechJ), 2024)
Patient safety is a top priority for health care facilities because it is related to the quality and good image of the hospital. The impact that occurs when health workers ignore patient safety is that patient care is prolonged, patients can experience physical and psychological trauma, disability and even death. Proper drug administration is influenced by several factors. One of these factors is the nurse behavior factor, where nurses do not apply the six principles of treatment in accordance with the Standard Operating Procedures (SOP) set by the hospital. The research aims to see the role of the Nurse in Charge in identifying the 6 correct drug administration. This research is of the analytical description type using observational methods. The population in the research were all nurses in the Anthurium 3 room with a sample of 14 respondents selected using total sampling. This study looked at the compliance of nurses in identifying the six correct principles as measured by a questionnaire on the implementation of the six correct principles of drug administration. The results of the study showed the accuracy of identifying 6 correct drugs, namely the correct drug with an accuracy of 74.1%, the correct dose of 70%, the correct time of 73.2%, the correct patient 64.2%, the correct route 87.5% and the correct documentation 65%. The implementation of the identification of the 6 correct drug administration can be carried out optimally if all nurses can carry out the protocol according to procedures based on the right drug, right time, right patient, right route, and right documentation.